2022
DOI: 10.3390/f13010059
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biotic and Abiotic Stress Factors on Development of European Ash Tissue Cultures

Abstract: Fraxinus excelsior L. is threatened by a variety of environmental factors causing a decline of the species. The most important biotic factors negatively affecting the condition of the F. excelsior population are fungi such as the pathogen Hymenoscyphus fraxineus. Abiotic factors with potentially harmful effect to the F. excelsior population are the accumulation of heavy metals and salinity in soils. Thus, the aim of this study was to investigate the impact of selected biotic and abiotic stress factors to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Despite several fungal species being able to reduce avocado production, new organisms with phytopathogenic activity can be found under open field conditions [ 4 ]. The phytopathogenic behavior of these organisms is usually associated with specific climatic and soil features in which the avocado plants grow [ 5 ]. The state of Puebla is the sixth largest producer of avocado in Mexico and the northern highlands of this state are considered a new zone dedicated to the production of this fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several fungal species being able to reduce avocado production, new organisms with phytopathogenic activity can be found under open field conditions [ 4 ]. The phytopathogenic behavior of these organisms is usually associated with specific climatic and soil features in which the avocado plants grow [ 5 ]. The state of Puebla is the sixth largest producer of avocado in Mexico and the northern highlands of this state are considered a new zone dedicated to the production of this fruit.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cadmium and lead show similar negative effects on callus tissue cultures and seedlings of common ash (F. excelsior) in laboratory conditions, and the toxic effect of lead on seedlings is slightly weaker than the toxic effect of cadmium (Nawrot-Chorabik et al 2022). Although there are no similar studies on narrow-leaved ash (F. angustifolia), it can be reasonably assumed that the effects of both heavy metals would be similar.…”
Section: Discussionmentioning
confidence: 98%
“…These studies are continued at the Department of Forest Ecosystem Protection. They refer to endophytic fungi as biotic stress factors, but are also extended to abiotic stress factors (heavy metals and salinity of the substrate) [53]. The setup is also useful in testing for production of biologically active metabolites, including compounds with potential medicinal applications.…”
Section: Discussionmentioning
confidence: 99%